Perspektif Hukum Islam Tentang Produk Gadai Emas pada Perbankan Syari’ah - Fawza, Rahmat (Jurnal Hukum Ekonomi Syariah : AICONOMIA, 2022)
Shari'ah gold pawn is a form of development of pawn (rahn) in classical fiqh. The gold pawning application in sharia banking is intended for the needs of customers who need short-term funds such as school entrance fees, Eid fees or short-term business capital. Gold pawning products are applied in Islamic banking through the DSN MUI fatwa Number 25/DSN-MUI/III/2002 dated June 26 2002 concerning rahn. Rahn Emas in Islamic banking should be utilized by customers who have urgent funding needs in the short term, but in reality, this mortgage product has led to deviations by some customers who use this product to speculate in search of profit from the difference in the selling price of gold, where the gold that is mortgaged will be sold when the price of gold soared. It's just that things like this don't always run smoothly, because the price of gold fluctuates, it will result in customers experiencing losses, if the customer has to sell the pledged gold when the price of gold falls. Not to mention the loss of customers who have to pay rental fees for storage and maintenance of goods per day. This research uses literature research methods that focus on literature review as the primary data source. And also equipped with studies from various supporting literature from secondary sources.